East Africa: Uganda - Agriculture, food security and climate change outlook - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Agriculture is the main economic sector, accounting for 27% of GDP, employing 73% of the labor force and contributing 46% of total exports. Agricultural production is primarily based on small scale subsistence farming, comprising a system of mixed agriculture with perennial and annual crops, as well as grazing throughout most of the districts across ten agroecological zones (AEZs). Agriculture in Uganda is mainly rain fed and based on subsistence farming; challenging the sustainability and food security of farmers, and making the sector highly vulnerable to weather variability, climate hazards (particularly droughts) and climate change.